Research on crashworthiness of self-similar nested metal multicellular tubes - HUANG CuiPing; DENG XiaoLin; CAI ZhenZhen (Jixie qiangdu)
The hierarchical multicellular structure exhibits good energy absorption characteristics, which can be widely used in the energy absorption devices of vehicles such as automobiles and airplanes. Two types of self-similar nested metal multi-cellular tubes were designed, the crashworthiness under axial impact was studied by numerical simulation. The results show that higher order multicellular tubes have better energy absorption capacity than lower order multicellular tubes, regardless of the same mass or wall thickness. With the same mass, the specific energy absorption ratio of higher order multi-cellular tubes is up to 36.45% and the crush force efficiency is up to 35. 42%. Under the same wall thickness, the maximum specific energy absorption and crush force efficiency of higher order multicellular tubes are increased respectively by 80.40% and 59.64%. The results show that the crashworthiness of the proposed self-similar nested metal multicellular tube is significantly improved compared with the traditional multicellular tube. Finally, the parametric study of the structural parameters such as order and wall thickness on the crashworthiness of self-similar nested metal multicellular tubes was carried out systematically.